THE EFFECTIVENESS OF USING PADLET IN TEACHING WRITING DESCRIPTIVE TEXT - Ilham Sukma Taufikurohman (Universitas Galuh, 2018)
This study was investigated the effects of Padlet on students’ descriptive text writing of Senior High School students as well as to find out their perceptions of using Padlet for learning descriptive text writing. In doing so, the subjects consisted of 54 students who were in tenth grade. Then they were divided into two equal experimental and control groups (N=27). Their age ranged between 16 and 17 years old. Gender of participants was not considered as a variable in the study. This study used convergent parallel mixed-method whereas pre-test and post-test were administrated to collect quantitative data and questionnaire was given to collect qualitative data. The experimental group was taught descriptive text writing via Padlet application, whereas the control group was taught by conventional media. Analyzing the data through the independent sample t-test revealed that with the help of Padlet application, the experimental group outperformed the control group in terms of writing descriptive text. Furthermore, the students had a positive attitude toward utilization of Padlet application.Keywords: Padlet, students, descriptive text writing